Collision Aware Distributed Multicast Routing Protocol for Vehicular Adhoc Networks - Ali Hamzah Najim (Zien Journals, 2023)
An effective multicast routing protocol becomes very essential to construct intelligent vehicular ad hoc networks (VANETs). Hence this network model consists of highly complex vehicle mobility achieving efficient routing is complicated in an urban environment. The data transmission between the sources to the destination becomes highly challenging because of the packet loss occurrence between the high speed vehicles. So that to achieve effective communication it is very essential to establish a collision free routing protocol to transmit the information among the source to the destination with high quality. For that purpose, in this paper Collision Aware Distributed Multicast Routing Protocol in VANETs (CDMRVANETs) is developed which consists of the subsets like routing design and the protocol functionalities. The routing design creates connections among each vehicle and with the infrastructure. Through the protocol functionalities the topology control is improvised with the help of Optimized Link State Routing Protocol (OLSR). Using the proposed CDMR routing protocol, the network collision is reduced that leads to increase the effectiveness of communication among the vehicles. The implementation of this method is done with NS2 in Ubuntu with SUMO mobility generator. The output parameters which are calculated in results section are packet delivery ratio, end-to-end delay, routing overhead, and energy efficiency and as well to performed comparative analysis the baseline methods which are concentrated are ECA-RSM and CAMD-DRF. At the end of this analysis it gets understood that the proposed CDMR routing protocol produce lower delay and overhead when compared with the earlier methods.
Keywords: Vehicular Ad hoc Networks; Collision Aware Model; Multicast Routing Protocol